Peritonitis secondary to non-traumatic small and large bowel perforation - Ilyas, Syed O.; Sheikh, Saeed A.; Muneeb, Muhammad D.; Makhdoomi, Mahmood A.; Naz, Erum; Bano, Sajila; Elsyed, Ashraf A. (International Surgery Journal, 2019)
Background: The objective of the study was to determine the outcome of secondary peritonitis in non-traumatic small and large bowel perforation in a secondary care hospital in the region of Ha’il, Kingdom of Saudi Arabia (KSA). Methods: This prospective study was conducted in a surgical unit of King Khalid Hospital, Ha’il Kingdom of Saudi Arabia, from 01 October 2013 to 30th June 2014. 30 patients were admitted through emergency room (ER). Every patient was enquired a detailed history about abdominal distension, abdominal pain, fever, constipation, vomiting, and gut motility. Clinical examination of the patient was done. Baseline investigations along with chest radiograph posterio-anterior (PA) view, abdominal radiograph with erect and supine views and ultrasound whole abdomen were included. All patients landed in the ER with peritonitis due to gastrointestinal perforation, regardless of their sex and age, were included. Peritonitis of primary cause or due to trauma, corrosive ingestion and anastomosis leak were excluded. Follow up of all the patients was done. Data was analyzed through SPSS software 16. Results: Out of 30 patients, 23 (76.66%) were male and 7 (23.33%) were female. Mean age 36.28±2.3 years. 80% presented with abdominal pain. Pneumoperitoneum on chest X-Ray was found in 21 (70%) patients. Duodenal perforation was the most common reason of peritonitis in 14 patients (46.66%). Surgical site wound infection is the commonest complication in 16 patients (53.33%). Conclusions: In conclusion, the outcome of secondary peritonitis in our Eastern population is perforation of the upper gastrointestinal tract and small bowel as the documented common cause, and wound infection as the commonest complication.